Which autoantibodies announce that lupus nephritis is on the way?. (June 2009) - Cornec, Divi; Gall, Emilie Cornec-Le; Segalen, Zazou; Hanrotel-Saliou, Catherine; Meur, Yannick Le; Renaudineau, Yves; Youinou, Pierre
Systemic lupus erythematosus is characterized by a wide assortment of clinical traits, along with a profusion of autoantibodies. In practice, lupus nephritis is rather common, and dsDNA reactivity is crucial. Not only is this antibody a valuable asset for the diagnosis of systemic lupus erythematosus, but it may also contribute to its pathogenesis. Consistent with this view is that titer of anti-dsDNA antibody reflects the presence of lupus nephritis. However, this may rise or drop, before or during a renal flare. Other autoantibodies would thus be of use in monitoring the disease. These include anti-αα-actinin, anti-C1q and antinucleosome antibodies. Yet, their prognostic value for lupus nephritis must be further investigated. The affinity of related autoantibodies for DNA should perhaps be taken into account, but more instrumental should be antinucleosome, anti-αα-actinin and anti-C1q antibodies. They are associated together, but each may be combined with high-affinity anti-dsDNA, and particularly with antibodies, to glomerular membrane-associated nucleosomes.